Meningkatkan Hasil Pembelajaran Tematik Tema 1 Sub Tema 1 Ciri-Ciri Mahkluk Hidup Melalui Penggunaan Media Video Animasi Pada Siswa Kelas III SD Negeri 1 Dofa Kecamatan Mangoli Barat Kabupaten Kepulauan Sula - Apridayani Marasabessy; Lismawati Baharuddin (Peneliti.net, 2022)
The purpose of this study was to improve learning outcomes in thematic learning by using animated video media for third grade students of SD Negeri 1 Dofa, West Mangoli District, Sula Islands Regency. This research is a classroom action research (CAR). The research was carried out in two cycles. The subjects of the research were the third grade students of SD Negeri 1 Dofa, totaling 20 students. Sources of data come from teachers and students. Data collection techniques are observation, interviews and evaluation/test questions. The results showed that through the use of learning animation video media can improve learning outcomes. The increase occurred in cycle II, learning outcomes increased so that it could support a quality learning. The conclusion of this research is the use of animated learning video media thematic theme 1 sub theme 1 characteristics of living things, can improve the learning outcomes of third grade students of SD Negeri 1 Dofa sub-district Mengoli Batar, Sula Islands district.